Pengaruh Return on Asset Dan Current Ratio Terhadap Pertumbuhan Laba Pada Perusahaan Sektor Customer Non-Cyclicals: The Effect of Return on Assets and Current Ratio on Profit Growth in Non-Cyclical Customer Sector Companies - Lisnawati Lisna; Ninuk Riesmiyantiningtias; Woro Dwi Hartanty (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
For companies, profit growth is an indicator that reflects financial performance, which may increase or decrease each year. This phenomenon is influenced by various internal and external factors. This study aims to provide empirical evidence regarding internal factors specifically financial ratios such as Return on Assets and Current Ratio and their ability to indicate a company's profit growth. This research employs a quantitative method using purposive sampling, resulting in a sample of 64 non-cyclical consumer sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The data used are secondary data obtained from the companies’ annual financial reports. The data analysis technique applied is multiple linear regression. The results of the study show that, partially, Return on Assets does not have a significant effect on profit growth, whereas the Current Ratio has a significant effect. Simultaneously, both Return on Assets and Current Ratio have a significant effect on profit growth.